Czech Koruna and Polish Zloty Currency Options : Information Contnent and Eu-Accession Implications - Mendez Morales, Armando (Washington, D.C. : International Monetary Fund, 2000)
Currency option implied volatility predicts more efficiently exchange rate volatility for the Polish zloty relative to the Czech koruna, reflecting differences in the frequency of central bank intervention in the foreign exchange market. A GARCH model shows a positive impact of the introduction of the Euro on exchange rate volatility for the Polish zloty (negative for the Czech koruna), related to its larger exposure to external shocks. For countries in transition to Euro integration, the implied trade-off between isolation from shocks and efficient signaling must be addressed based on the risk of exchange rate misalignment at the time of monetary conversion.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet